Analysis of the human B cell repertoire following vaccination - Galson, J (2016)
A diverse B cell repertoire is essential for recognition and response to infectious and vaccine antigens. High-throughput sequencing of B cell receptor (BCR) genes can now be used to study the B cell repertoire at a depth which reflects its true diversity. As a relatively new technology, there is little information on the structure of the repertoire at baseline, whether antigen-specific changes can be detected from the total repertoire following antigen stimulus, and what the potential clinical applications of BCR repertoire sequencing are. In this thesis, robust laboratory and bioinformatic techniques were developed for studying the BCR repertoire. These were then applied to healthy participants to assess inter- and intra-individual variation in the repertoire. Hepatitis B vaccination was then used as a model system to determine how the repertoire responded to both primary and booster vaccination. Tracking repertoire dynamics following booster vaccination identified the presence of time-limited changes in the total BCR repertoire following stimulation. Cell sorting and sequencing of vaccine-specific cells in addition to sequencing the total repertoire allowed deconvolution of the vaccine- specific response from background repertoire fluctuations. Studying the response to primary vaccination showed the same time-limited changes, and revealed that a surprising number of the B cells activated appear to be derived from memory cells, and activated by the vaccine in a cross-reactive manner. More specific applications of BCR repertoire sequencing were then investigated in the context of meningo- coccal and influenza vaccine studies. These were able to distinguish the different cell subsets activated in response to meningococcal polysaccharide and conjugate vaccines, and shed light on how the AS03 adjuvant increases pandemic influenza vaccine immunogenicity. In summary, presented in this thesis are some of the first BCR repertoire data following Hepatitis B, meningococcal and influenza vaccination. These data have increased our fundamental understanding of the BCR repertoire, and how this responds to vaccination. Insights from these data raise promise for the application of this technology to clinical settings for vaccine evaluation, disease diagnostics and monitoring, and therapeutic antibody discovery, and have provided a foundation for many further studies.